INVESTIGATION OF MOLECULAR MOBILITY IN A MODIFIED EPOXY BINDER USING THE DIELECTRIC LOSS TANGENT METHOD - STUKHLIAK, PETRO; TOTOSKO, OLEH; STUKHLIAK, DANYLO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
—brought about by incorporating dispersed additives into the polymeric matrix—markedly alters the relaxation patterns of the macromolecule at the interfacial zone. A comprehensive study was carried out to investigate the influence of electric spark hydro-impact (ESHI) treatment on the structure formation processes and relaxation behaviour of epoxy-based composites. The experimental results demonstrated that the application of ESHI leads to a noticeable shift of relaxation maximum temperatures toward higher values by approximately 30–40 K, accompanied by variations in the width and intensity of dielectric loss peaks. These changes are indicative of an increased degree of molecular cross-linking, enhanced network density, and the development of more organized surface layers within the polymer matrix. Furthermore, the modification of the oligomer by ESHI promotes the formation of a spatially homogeneous and energetically stable structure, resulting in improved thermo-mechanical stability. The combined effect of ESHI and the incorporation of the DEG-1 plasticiser has been shown to positively influence the segmental mobility of macromolecular chains, facilitating a more flexible yet robust polymer network. This synergy contributes to improved adhesive strength at the filler–matrix interface and greater resistance to thermal degradation. Overall, the obtained data confirm that ESHI treatment represents an efficient pre-processing technique for tailoring the molecular architecture of epoxy composites, providing a promising approach for enhancing their operational reliability and durability in demanding environments.
Keywords: epoxy matrix; composite materials; structure formation; relaxation processes; dielectric losses; segmental mobility